Mapping white matter structural and network alterations in betel quid-dependent chewers using high angular resolution diffusion imaging - Huang, Weiyuan; Liu, Tao; Chen, Huijuan; Fu, Qingqing; Fu, Lili; Xu, Xiaolin; Liu, Liting; Guo, Yihao; Balasubramanian, Priya S.; Chen, Feng (Frontiers in Psychiatry, 2022)
Abstract Background: To evaluate brain white matter diffusion characteristics and anatomical network alterations in betel quid dependence (BQD) chewers using high angular resolution diffusion imaging (HARDI). Methods: The current study recruited 53 BQD chewers and 37 healthy controls (HC) in two groups. We explored regional diffusion metrics alternations in the BQD group compared with the HC group using automated fiber quantification (AFQ). We further employed the white matter (WM) anatomical network of HARDI to explore connectivity alterations in BQD chewers using graph theory. Results: BQD chewers presented significantly lower FA values in the left and right cingulum cingulate, the left and right thalamic radiation, and the right uncinate. The BQD has a significantly higher RD value in the right uncinate fasciculus than the HC group. At the global WM anatomical network level, global network efficiency (p=0.008) was lower and Lp (p=0.016) was higher in the BQD group. At the nodal WM anatomical network level, nodal efficiency (p<0.05) was lower in the BQD group. Conclusions: Our findings provide novel morphometric evidence that brain structural changes in BQD are characterized by white matter diffusivity and anatomical network connectivity among regions of the brain, potentially leading to the enhanced reward system and impaired inhibitory control.